How to publish biomedical research in "non-predatory" journals: a discussion and notes from experts - Askhat Myngbay; Zulfiya Orynbayeva; Kuat Oshakbayev; Abduzhappar Gaipov (National Scientific Medical Center, 2018)
On behalf of Editorial and Advisory Board of Journal of Clinical Medicine of Kazakhstan